Does the Kis-Balaton Water Protection System (KBWPS) Effectively Safeguard Lake Balaton from Toxic Cyanobacterial Blooms? - Zoran Marinović (Microorganisms, 2021)
Lake Balaton is the largest shallow lake in Central Europe. Its water quality is affected by its biggest inflow, the Zala River. During late 20th century, a wetland area named the Kis-Balaton Water Protection System (KBWPS) was constructed in the hopes that it would act as a filter zone and thus ameliorate the water quality of Lake Balaton. The aim of the present study was to test whether the KBWPS effectively safeguards Lake Balaton against toxic cyanobacterial blooms. During April, May, July and September 2018, severe cyanobacterial blooming was observed in the KBWPS with numbers reaching up to 13 million cells/mL at the peak of the bloom (July 2018). MC- and STX-coding genes were detected in the cyanobacterial biomass. Five out of nine tested microcystin congeners were detected at the peak of the bloom with the concentrations of MC-LR reaching 1.29 µg/L; however, accumulation of MCs was not detected in fish tissues. Histopathological analyses displayed severe hepatopancreas, kidney and gill alterations in fish obtained throughout the investigated period. In Lake Balaton, on the other hand, cyanobacterial numbers were much lower; more than 400-fold fewer cells/mL were detected during June 2018 and cyanotoxins were not detected in the water. Hepatic, kidney and gill tissue displayed few alterations and resembled the structure of control fish. We can conclude that the KBWPS acts as a significant buffering zone, thus protecting the water quality of Lake Balaton. However, as MC- and STX-coding genes in the cyanobacterial biomass were detected at both sites, regular monitoring of this valuable ecosystem for the presence of cyanobacteria and cyanotoxins is of paramount importance.